Projected Increases in Global Terrestrial Net Primary Productivity Loss Caused by Drought Under Climate Change - Cao, Dan; Zhang, Jiahua; Han, Jiaqi; Zhang, Tian; Yang, Shanshan; Wang, Jingwen; Prodhan, Foyez Ahmed; Yao, Fengmei (Earth's future, 2022)
Understanding present and future impacts of drought on the terrestrial carbon budget is of great significance to the evaluation of terrestrial ecosystem disturbance and terrestrial carbon sink. Here, we evaluate the effect of vegetation net primary productivity (NPP) associated with drought through the difference between the mean NPP in the drought and normal years during a specific time period (30 years). Then, the NPP effects in different vegetation types and climatic zones under baseline stage (1981–2010) and future climate scenarios (RCP2.6, RCP4.5, and RCP8.5) is assessed. The results indicate that the negative NPP extremes are captured in most regions, except for the high‐latitude in the Northern Hemisphere. The NPP loss caused by extreme droughts in 2071–2100 is largest under RCPs, followed by the effects of severe and moderate droughts. Regionally, central United States, southern Africa, central Asia, India, Amazon tropical rainforest, and Australia are projected to experience a significant increase in negative NPP extremes and most of these regions are in arid and semi‐arid and tropical rain forest areas. In contrast, tropical Asia suffers little drought effects. For different vegetation, Evergreen Broadleaf Forest, Closed Shrubland, Open Shrubland, Croplands, and Grassland are the most affected by drought. The largest NPP loss occurs in most part of regions under RCP4.5 scenario, not RCP8.5. Climate change is projected to play the largest role in aggravating the risk of drought‐induced NPP reduction. And meanwhile, the adverse effects of drought on vegetation may be resisted through rational fertilizer utilization and land management in future. Plain Language Summary Drought is already the most widespread factor affecting terrestrial net primary productivity (NPP) via direct physiological effects, such as water limitation and heat stress. Nevertheless, the effects of drought on terrestrial ecosystems under future climate change are still highly uncertain. In this study, we assess and compare the present and future impact of drought on vegetation net primary productivity. The results suggest that global drought events are projected to be intensified and frequent in the coming decades. Drought‐related NPP reduction is prevalent especially in the arid and semi‐arid areas and tropical regions at the end of 21st century. Extreme drought depresses NPP most under RCPs, followed by severe and moderate droughts. For vegetation, the adverse impact on NPP induced by drought under RCPs is increasingly significant in Evergreen Broadleaf Forest, Grassland, Savanna, and Cropland. Climate change is projected to play the largest role in aggravating the risk of drought‐induced NPP reduction. These results highlight the growing vulnerability of ecosystem productivity to droughts, implying increased adverse impacts of these climate extremes on terrestrial carbon sinks. Key Points Net primary productivity (NPP) reduction associated with drought is prevalent especially in the arid and semi‐arid areas and tropical regions Adverse impact of drought on NPP under RCPs is large in Evergreen Broadleaf Forest, Shrubland, Grassland, and Cropland The largest NPP loss occurs under RCP4.5. Climate change plays the largest role in aggravating the risk of drought‐induced NPP reduction